Oral candidiasis and denture stomatitis in diabetic patients: Systematic review and meta-analysis - MARTORANO-FERNANDES,Loyse (2020)
Abstract Here, the prevalence of oral candidiasis and denture stomatitis among diabetic patients compared to healthy ones was summarized through a systematic review with meta-analysis. Medline, Scopus, Web of Science, Lilacs, Cochrane Library, Embase, and the grey literature were searched without restriction, until May 2020. Eligibility criteria were established, data were extracted, and quality assessment was conducted by two trained examiners. Qualitative synthesis was based on the recommendations of Fowkes and Fulton. Two meta-analyses were performed on studies investigating patients with: a) oral candidiasis and b) denture stomatitis. Out of 6034 screened studies, seven were eligible for qualitative and quantitative synthesis; of these, three evaluated oral candidiasis and four evaluated denture stomatitis. Qualitative synthesis showed that the main methodological problems of the studies included sample size, source of controls, matching, and randomization. Diabetic patients had a similar chance of developing oral candidiasis to non-diabetic patients (OR1.40 [0.96; 2.04], p = 0.08, I2 = 94%). However, diabetic patients had a higher chance to present denture stomatitis compared to non-diabetic patients (OR 1.92 [1.42, 2.59] p < 0.0001, I2 = 0%). Therefore, diabetic patients have a higher chance of developing denture stomatitis compared to non-diabetic patients. However, for all analyses, the certainty of the evidence was considered to be very low.